Applying CHC Models to Reasoning in Fictions - Urtubey, Luis; Massolo, Alba (2022)
Fil: Urtubey, Luis. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Filosofía; Argentina.